A Computational Approach for the Calculation of Temperature Distribution in Casting-Mould Heterogeneous System with Fractional Order. (26th July 2022) - Luo, Xiankang; Nadeem, Muhammad; Asjad, Muhammad Imran; Abdo, Mohammed S.
Abstract : The purpose of this paper is to investigate the approximate solution of the casting-mould heterogeneous system with Caputo derivative under the homotopy idea. The symmetry design of the system contains the integer partial differential equations and the fractional-order partial differential equations. We apply Yang transform homotopy perturbation method (Y T-HPM) to find the approximate solution of temperature distribution in the casting-mould heterogeneous system. The Y T-HPM is a combined form of Yang transform (Y T) and the homotopy perturbation method (HPM) using He's polynomials. Some examples are provided to demonstrate the superiority of the suggested technique. The significant findings reveal that Y T-HPM minimizes the enormous without imposing any assumptions. Due to its powerful and robust support for nonlinear problems, this approach presents a remarkable appearance in the functional studies of fractal calculus.